Business Forums Pave the Way to Ethical Decision Making: The Mediating Role of Self-Efficacy and Awareness of a Value-Based Educational Institution - Blewitt, J. C. (Journal of business ethics, 2018)
In the midst of recent ethical decision-making failures in business in the past ten or more years, businesses are beginning to prioritize the moral fiber of their new-hire business graduates. In addition to academic performance, intellectual drive, and personality match, perhaps there are other key characteristics that employers seek which speak to the importance of ethical decision makers in practice. The question remains, how can academic institutions help instill such values into their students so that ethical decision making transcends their lives? This article suggests that experiential learning through an institutional-sponsored business forum can help enhance an individual’s self-efficacy and awareness of the school’s value-based education, which ultimately will lead students towards ethical decision making in practice. Five years of survey data collected at business forum events suggests that business forums are making a difference in the students’ self-assessed abilities to show greater self-efficacy, better ethical decision making, and an increased awareness of their institution’s value-based education. Specifically, data collected illustrate a mediating effect of self-efficacy and awareness of a value-based education en route to ethical decision making. Further, support is found for the primary hypothesis that attendance at business forums does result in a higher propensity to make ethical decisions. Because of these positive findings, higher education institutions looking to place a greater emphasis on the ethical leadership of their business students may want to explore adding such experiential learning programs.